2014
DOI: 10.1530/eje-13-0557
|View full text |Cite
|
Sign up to set email alerts
|

Intensive insulin therapy increases sex hormone-binding globulin in newly diagnosed type 2 diabetic patients

Abstract: Objective: Many studies have shown that low sex hormone-binding globulin (SHBG) is associated with insulin resistance, but only few studies have examined how serum SHBG is regulated by insulin in humans. This interventional study aimed to investigate the effect of insulin therapy (IT) on serum SHBG levels in newly diagnosed type 2 diabetic patients. Methods: A total of 80 newly diagnosed type 2 diabetic subjects were enrolled and randomly grouped into a 2-week intensive IT with/without metformin. Serum SHBG, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
3
12
0
1
Order By: Relevance
“…Recently, evidence for the role of insulin in direct modulation of the hypothalamic–pituitary–gonadal axis has been suggested by several studies. In a randomized controlled trial of diabetic men, SHBG and total testosterone levels increased after 2 weeks of intensive insulin treatment with/without metformin, noted especially in the group treated without metformin. Normal insulin level is necessary for Leydig cells function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, evidence for the role of insulin in direct modulation of the hypothalamic–pituitary–gonadal axis has been suggested by several studies. In a randomized controlled trial of diabetic men, SHBG and total testosterone levels increased after 2 weeks of intensive insulin treatment with/without metformin, noted especially in the group treated without metformin. Normal insulin level is necessary for Leydig cells function.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a randomized, double‐blinded, case–control clinical trial has reported a significant reduction in serum total testosterone levels (by 1.1 nmol/L), calculated free testosterone (cFT) and bioavailable testosterone (BioT) in eugonadal men with type 2 diabetes after treatment of pioglitazone for 6 months. Researchers also found increased serum sex hormone‐binding globulin (SHBG) and increased TT levels in men with newly diagnosed type 2 diabetes who were treated with an intensive insulin treatment strategy. Above all, the impacts on testosterone levels in men with type 2 diabetes differs to that of antidiabetic treatments, showing that changes in testosterone levels occur in such a way that might not be correlated directly to the blood glucose changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, no correlation was found between SHBG and fasting insulinemia [4]. In addition, the direct effects of insulin administration on SHBG plasma levels were examined in two different studies and in both a significant increase rather than a decrease in SHBG plasma levels was reported [35,58]. Since insulin has a powerful anti-inflammatory action and proinflammatory cytokines downregulate SHBG production (see below), it could be postulated that a SHBG increase after insulin administration is due to the insulin-mediated inhibition of proinflammatory cytokines.…”
Section: Shbg Expression and The Role Of Insulinmentioning
confidence: 99%
“…Genetic evidence has also shown that an alteration in SHBG gene expression directly affects serum levels as well as the overall risks of developing T2DM. 50,51 Recently, insulin therapy has been found to increase SHBG through improved insulin resistance 52 suggesting a relationship between these factors in MetS.…”
Section: Discussionmentioning
confidence: 99%